2009
DOI: 10.1177/0961203309104862
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Arterial Vascular Events in PROFILE: A Multiethnic Lupus Cohort

Abstract: Summary The objective of this study was to determine the factors associated with the occurrence of arterial vascular events in a multiethnic systemic lupus erythematosus (SLE) cohort. The PROFILE cohort, comprised of SLE patients (n=1,333) of defined ethnicity from five different U.S. institutions, was studied to determine demographic, clinical and biological variables associated with vascular events. An arterial vascular event (first episode) was either a myocardial infarction, angina pectoris and/or a vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 51 publications
7
42
2
3
Order By: Relevance
“…SLE may involve multiple organs, and vascular events including ischemic stroke, however, acute myocardial infarction and peripheral arterial occlusive disease are not uncommon (3)(4)(5)(6)(7)(8). Additionally, there are few studies which have compared the risk of developing future ischemic stroke in SLE with that of the general population among Caucasians (9,(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SLE may involve multiple organs, and vascular events including ischemic stroke, however, acute myocardial infarction and peripheral arterial occlusive disease are not uncommon (3)(4)(5)(6)(7)(8). Additionally, there are few studies which have compared the risk of developing future ischemic stroke in SLE with that of the general population among Caucasians (9,(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of SLE varies widely, with periodic flare-ups of symptoms impacting multiple organ systems and resulting in potentially lifethreatening complications (1)(2)(3). Recently, an association has been noted between premature atherosclerosis and this chronic inflammatory disease (3)(4)(5)(6)(7)(8). Accumulating evidence has shown that atherosclerosis is not just a cholesterol storage disorder in vasculature but a sustained, dynamic and chronic inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low hemoglobin levels are associated with decreased oxygencarrying, inflammatory response, alterations in blood viscosity and impairment of cerebral autoregulation (9,10). Nonetheless, data with regard to the relationship between anemia status upon admission and short-and long-term outcome post-stroke are scarce (11)(12)(13). There are no specific recommendations as to the management of acute stroke patients with anemia other than sickle cell disease (14).…”
Section: Introductionmentioning
confidence: 99%
“…Cohort and cross-sectional studies reveal that the incidence of CVD in SLE patients ranges from 6.2% to 13% [3][4][5][6][7][8] depending on the duration of observation. Women with lupus in the 35-to 44-year-old age group were over 50 times more likely to experience a myocardial infarction when compared to age-and sex-matched controls [9].…”
Section: Introductionmentioning
confidence: 99%